1993
DOI: 10.1161/01.str.24.8.1125
|View full text |Cite
|
Sign up to set email alerts
|

Does low-dose acetylsalicylic acid prevent stroke after carotid surgery? A double-blind, placebo-controlled randomized trial.

Abstract: Background and Purpose: The aim of this randomized double-blind, placebo-controlled trial was to evaluate whether neurological deficits could be prevented with low-dose acetylsalicylic acid (ASA) as an adjunct to carotid endarterectomy.Methods: A total of 232 patients were randomized to two groups, 75 mg/d ASA starting preoperatively and continued for 6 months (n=117) or placebo (identical tablets) (n=115). The patients were followed up regularly for 1 year.Results: The groups were well matched regarding labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0
4

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(75 citation statements)
references
References 18 publications
1
70
0
4
Order By: Relevance
“…Another trial enrolled 232 subjects to 75 mg aspirin or placebo started before CE and continued for 6 months (Class I). 19 Although likely underpowered, this trial demonstrated fewer strokes without recovery in those subjects randomized to aspirin compared with placebo at 1 month (zero strokes vs 7 strokes, p ϭ 0.003) and 6 months (2 strokes vs 11 strokes, p ϭ 0.01).…”
Section: What Is the Ideal Dose Of Aspirin Preoperatively In Patientsmentioning
confidence: 86%
“…Another trial enrolled 232 subjects to 75 mg aspirin or placebo started before CE and continued for 6 months (Class I). 19 Although likely underpowered, this trial demonstrated fewer strokes without recovery in those subjects randomized to aspirin compared with placebo at 1 month (zero strokes vs 7 strokes, p ϭ 0.003) and 6 months (2 strokes vs 11 strokes, p ϭ 0.01).…”
Section: What Is the Ideal Dose Of Aspirin Preoperatively In Patientsmentioning
confidence: 86%
“…2,3 Aspirin in a dose of 75 mg/d was shown to be effective in reducing the risk of acute myocardial infarction (MI) or death in patients with unstable angina 4 and chronic stable angina, 5 as well as in reducing stroke or death in patients with transient cerebral ischemia 6 and the risk of postoperative stroke after carotid endarterectomy. 7 In the European Stroke Prevention Study (ESPS)-2, aspirin 25 mg twice daily was effective in reducing the risks of stroke and of the composite outcome stroke or death in patients with prior stroke or transient ischemic attack (TIA). 8 Moreover, in the European Collaboration on Low-dose Aspirin in Polycythemia vera (ECLAP) trial, 9 aspirin 100 mg/d was effective in preventing thrombotic complications in patients with polycythemia vera, despite a higher-than-normal platelet count.…”
Section: The Optimal Dose Of Aspirinmentioning
confidence: 99%
“…Interestingly, when surgeons are not aware if aspirin was used or not, they often cannot distinguish, based on the type of bleeding, patients on aspirin from those who have discontinued. 40 The American College of Chest Physicians guidelines for the perioperative management of antithrombotic therapy have identified a group of surgeries and procedures that appear to be associated with a high risk for bleeding in the context of perioperative anticoagulant and antiplatelet drug use. 41 An alternative approach coming from a joint national consensus defined the interventions at greater risk of bleeding within an array of different surgeries or invasive procedures (Table 1).…”
Section: Bleeding Riskmentioning
confidence: 99%